Living Machines with Gentle Looks: Materiality and Animal Body in Modernizing Finnish Animal Husbandry - Kaarlenkaski, Taija (Humanimalia, 2019)
This paper discusses the modernization of cattle tending in late nineteenth-century and early twentieth-century Finland from viewpoints of materiality and embodiment. In accordance with new materialist theories, both human and bovine bodies are seen as material-discursive phenomena constituted in the entanglement of material and cultural practices. The paper investigates how bovine bodies, embodiment, and agency were represented and conceptualized, and what kind of qualities “good cows” had at the time. The materials used in the study consist of answers sent to an ethnographic questionnaire, as well as ten cattle tending guidebooks, all dating back to the turn of the twentieth century. It is argued in the paper that questions of agency and subjectivity in modernizing animal husbandry were multidimensional, and that the consequences of increasing objectification of bovine bodies were not just negative for cattle.